The role of Cas8 in type I CRISPR interference - Cass, Simon; Haas, Karina; Stoll, Britta; Alkhnbashi, Omer; Sharma, Kundan; Urlaub, Henning; Backofen, Rolf; Marchfelder, Anita; Bolt, Edward (Portland Press, 2015)
CRISPR (clustered regularly interspaced short palindromic repeat) systems provide bacteria and archaea with adapt- ive immunity to repel invasive genetic elements. Type I systems use ‘cascade’ [CRISPR-associated (Cas) complex for antiviral defence] ribonucleoprotein complexes to target invader DNA, by base pairing CRISPR RNA (crRNA) to protospacers. Cascade identifies PAMs (protospacer adjacent motifs) on invader DNA, triggering R-loop formation and subsequent DNA degradation by Cas3. Cas8 is a candidate PAM recognition factor in some cascades. We analysed Cas8 homologues from type IB CRISPR systems in archaea Haloferax volcanii (Hvo) and Methanothermobacter ther- mautotrophicus (Mth). Cas8 was essential for CRISPR interference in Hvo and purified Mth Cas8 protein responded to PAM sequence when binding to nucleic acids. Cas8 interacted physically with Cas5–Cas7–crRNA complex, stimulating binding to PAM containing substrates. Mutation of conserved Cas8 amino acid residues abolished interference in vivo and altered catalytic activity of Cas8 protein in vitro. This is experimental evidence that Cas8 is important for targeting Cascade to invader DNA.